Predicting & explaining intention to adopt green concepts among housing developers - Lau, Jasmine; Hashim, Ahmad Hariza; Abu Samah, Asnarulkhadi (Bridge Center, 2015)
This study aimed to determine the factors that predict the behavioral intentions to adopt green concepts among housing developers using the TPB model. This study adopted quantitative approach with a complementary qualitative data collection procedure. A total of 87 cases were collected from questionnaire survey. Correlation analysis showed that intention to adopt green concept was correlated most strongly with PBC (r = .713, p < .01) and subjective norm (r = .606, p < .01) and less strongly with attitude (r = .584, p < .01). Regression model was statistically significant, F(3, 83) = 57.11, p < .001, and accounted for approximately 67% of the variance of intention to adopt green concepts (R2 = .67). PBC was found to be the best predictor (β = .45, p < .001), followed by subjective norm (β = .34, p < .001) and attitudes (β = .25, p < .01). Conclusion and limitation of this study were also discussed.